Teaching for Understanding: A transformative and relevant pedagogical approach for SENA - Puentes, Yecid
A simple but powerful 5-element framework, with performance-based design and staging of classroom projects, has proven to be one of the most useful action ideas for teachers in recent decades. Born as an inquiry project in pedagogy among some of the researchers from Project Zero of the Graduate School of Education at the prestigious Harvard University, Teaching for Understanding has served teachers from various countries, of basic, secondary and university education, as a very useful tool to design what have been called class systems, directed towards a deep understanding of complex topics. In this article, said Teaching for Understanding is exposed in the context of SENA.